Pengaruh Gaya Hidup Terhadap Pendapatan Pada Generasi Milenial - pakri Fahmi (Universitas Prof.Hazairin,SH Bengkulu, 2021)
This study aims to examine the effect of Income on Lifestyle in the millennial generation in Bengkulu City. This research was conducted in the city of Bengkulu. The number of samples in this study were 100 respondents. The results showed that 48.2% of the income variable was able to explain the lifestyle variables of the millennial generation in Bengkulu City. Based on the results of simultaneous and partial tests, income variables affect the lifestyle of the millennial generation.